The maze of bones - Riordan, Rick. (New York : Scholastic, 2008)
Amy and Dan, members of the powerful Cahill family, try to uncover the thirty-nine clues which will reveal the secrets of their lineage and find out what really happened to their parents.
May include game cards in cover page.
4.5
3-6
Keywords: Family -- History -- Juvenile fiction; Cryptography -- Juvenile fiction; Genealogy -- Juvenile fiction; Family -- History -- Fiction; Cryptography -- Fiction; Genealogy -- Fiction; Mystery and detective stories; Family -- History -- Fiction; Cryptography -- Fiction; Genealogy -- Fiction; Mystery fiction; Code and cipher stories; Mystery fiction